Broadband Three-Section Branch-Line Coupler Realized by Ridge Gap Waveguide Technology From 12 to 20 GHz - Parisa Mahdavi; S. Esmail Hosseini; Pedram Shojaadini (IEEE Access)
The novel ridge-gap waveguide (RGW) technology which uses an entire metal structure has various advantages at high frequencies, such as broad bandwidth, low loss, low sensitivity to manufacturing errors, and uncomplicated integration with passive and active components. In this paper, a broadband RGW-based three-section branch-line coupler in the frequency band of 12 to 20 GHz is proposed, simulated, and experimentally demonstrated. The proposed structure employs four short stubs at the branches with a quarter wavelength for impedance matching. Also, four steps have been added for better power division on the coupling branch lines. The proposed structure with WR62 transition shows low-loss, equal-power division, 90-degree with good impedance matching, and isolation in the frequency band of 12–20 GHz containing the Ku band, and, the measured results are in good agreement with the simulations. The introduced structure can be extended to an arbitrary broadband power divider/combiner, which can find various applications, such as in array antenna feed networks and solid-state power amplifiers. It can be redesigned for broadband, high-power, and low-cost millimeter-wave applications.